PARADOKSALITAS REPRESENTASI GENDER DALAM DRAMA KOREA GENDER BENDER “MR. QUEEN” - Fina Zahra; Fadli Muhammad Athalarik (Jurnal Komunikasi dan Budaya, 2022)
This report attempts to explain and criticize gender representation in the gender bender genre drama “Mr. Queen” which overturned gender and its relation to gender discourse in South Korea and in Indonesia. Using Sara Mills' critical discourse analysis, it is evident that the gender representation in “Mr. Queen” is paradoxical; as if offering a gender discourse that breaks the dominant discourse, but in fact it still represents woman as passive subject who continue to be exploited